Diagnosis of the Internal Control System at the new and digna life Foundation of the city of Montería - Causil-Lengua, Carlos A.; Bravo-Yepes, Alexander; Becerra-Ossa, Jhennys P. (EFIM Ediciones, 2021)
This research focused on carrying out a diagnosis of the Internal Control System at the New and Digna Life Foundation of the city of Montería, using the COSO internal control model. The sample unit corresponds to the Foundation, taking for the study 12 subjects participating in the managerial, administrative, operational and control positions that were directly related to the control activities; the instruments used for data collection were a questionnaire containing 18 items and a check or checklist, used to expand the information obtained through the questionnaire applied. As a result of the investigation, it was possible to obtain that the organization under study is exposed to various risks of a financial, economic and legal nature, since there are failures in the implementation and structuring of the Internal Control System, where it could be evidenced that no There is a designated or responsible area for managing it, which affects the independence of one process from another when establishing controls and carrying out the preventive and / or corrective measures that may take place. The Internal Control System is an essential tool in this type of organizations because it helps minimize risks and make better decision-making, resulting in greater operationality and process flow.